Analyze the future development of college students' entrepreneurship from the perspective of"Internet Plus" - Ma, Haizhong (2024)
The emergence of The Times has led to a significant impact on the entrepreneurial behavior of college students due to the fast advancement of Internet technology. The ability to accurately identify entrepreneurial possibilities plays a crucial role in determining the success or failure of individual entrepreneurship. The objective of this research is to examine the potential impact of social media on the identification and promotion of entrepreneurial possibilities among college students. This paper presents a comprehensive review of the existing research on the relationship between social media and entrepreneurship among college students in the field of entrepreneurship. The study presents a conceptual framework consisting of five aspects and six assumption.These dimensions include entrepreneurial awareness, social capital,previous knowledge，social media , and entrepreneurial opportunity recognition. A totally of 234 credible questionnaires were collected via the use of questionnaire creation, survey administration, and data screening techniques among college students. The administration of validity and reliability tests, hypothesis testing , correlation analysis and on the received survey form data has validated the final six hypotheses.. The empirical evidence indicates that the use of social networks significantly influences the sense of entrepreneurial potential among college student entrepreneurs. The regulating function in this process is played by past knowledge and entrepreneurial savvy. Simultaneously, it is noteworthy that past knowledge plays a crucial and constructive role in fostering entrepreneurial awareness of college students. Research has shown that the existence of social asset has directly and favorable effect on the capacity of university students to recognize entrepreneurial prospects. Moreover, the effect of social network on university students' cognition of entrepreneurial prospects is significantly shaped by social capital. Moreover, this study offers validation that different classifications of social network platforms have unique impacts on the entrepreneurial pursuits of university students.